Decolonial Post-Tribal Interpretation: Proto-Tribal Socio-Economic Contestation in 3 Reigns 12:24p-t - West, Gerald (Old Testament Essays, 2023)
This article reflects on the socio-economic and tribal dimensions of both 3 Reigns 12:24p-t and the post-1994 South African transition. Mahmood Mamdani’s recent book, Neither Settler nor Native, provides an analysis of political decolonisation in post-apartheid South Africa, in which he identifies two areas of failure within the significant gains made during South Africa’s transition from apartheid to democracy—socio-economic justice and tribalisation. These two areas are the unfinished business of our substantive decolonisation of the political. In this article, I use Mamdani’s analysis as an exegetical dialogue partner, probing the socio-economic and tribal dimensions of 3 Reigns 12:24p-t and identifying this text as a proto-tribal text which documents the emergence of tribal economics. Methodologically, this article establishes a to-and-fro tripolar movement between the contemporary South African context and the biblical text. https://doi.org/10.17159/2312-3621/2023/v36n1a7